Survival of Patients on Maintenance Hemodialysis Base on Comorbidity of Cardiovascular Disease in Persahabatan Central General Hospital 2015-2019 - Mila Fitriaty; Nurhayati Adnan; Muhammad Syafiq (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2021)
Chronic kidney disease is the progressive loss of kidney function over months or years. The significant increase in new cases of chronic kidney disease is in line with the increasing number of patients undergoing hemodialysis as kidney replacement therapy in an effort to survive. Comorbid cardiovascular disease is a major risk factor for morbidity and mortality with chronic kidney disease. The study was conducted to determine the survival of hemodialysis patients in the group with comorbid cardiovascular disease and the group without comorbid cardiovascular disease. This study used a retrospective cohort design. The location of this study was conducted at Persahabatan Central Public Hospital, DKI Jakarta, and used secondary data from the hospital information system data from 2015 to 2019. The variables significantly related to the survival of patients undergoing hemodialysis with comorbid cardiovascular disease were age, complications of anemia, diabetes mellitus, and hypertension. The age variable has a p-value of 0.029 with an HR of 1.54 (95% CI OR 1.043-2.262). The anemia variable has a p-value of 0.013 with an HR of 1.60 (95% CI 1.117-2.515). The diabetes mellitus variable has a p-value of 0.000 with HR2.71 (95% CI 1.780-4.11). The hypertension variable has a p-value of 0.004 with HR1.79 (95% CI 1.208-2.646). In conclusion, patients undergoing hemodialysis with comorbid cardiovascular disease have a risk of death of 0.76 times compared to patients undergoing hemodialysis with the comorbid non-cardiovascular disease. This study's internal validity was not good due to selection bias and non-differential misclassification information bias. Thus, the results of this study cannot be generalized.